Synthesis of ketimine and evaluation of its anticorrosion avtivity - Halla Abdelbaki; Elhani Kenza; Rebat Oum elkheir Bachar (University Of Eloued جامعة الوادي, 2020)
This work is inscribed in the frame of synthesis of 3 -[(1E)-N-(2-aminophenyl)ethanimidoyl]-4-hydroxy—methyl-2H-pyran-2-one from the DHA which condenses with o-PDA and its evaluation as a corrosion inhibitor in HCl 1M solution. To measure the anti corrosion action we used the method with weight loss. The tests highlighted, concerning the corrosion of copper, an inhibition efficiency of 42.10%.
Intervention
Keywords: DHA; o-PDA; Ketimine; weight loss method; Anticorrosion activity